Immune status against measles among infants and pregnant women in selected municipalities - Geraldino, Nelson T. (1993)
A study to document the immune status against measles in rural areas, was done in the barangays outside of the poblacion in Tigbauan and Guimbal in Iloilo and Alfonso and Aguinaldo in Cavite, in December 1991 and August 1992, respectively. Measles agglutination-inhibiting antibody titers were determined from 468 infants from the newborn period up to 9 months of age, as well as 20 pregnant women of the Iloilo group. Subjects from the Cavite group consisted of 316 infants of the same age group and 200 pregnant women. Only 2.78 (13/468) of the infants from the Iloilo group and 2.22 (7/316) from the Cavite group were positive for measles antibodies at 1:5 serum dillution, which has been suggested to be the minimum titer that can neutralize the virus. (Lennon and Black, 1986; Albrecht, 1977) For pregnant women, 45 (9/20) from the Iloilo group and 38 (76/200) from the Cavite group were positive for measles antibodies at 1:5 serum dilution. The low proportion of infants with protective levels of measles antibodies means that many of the tested infants are not able to acquire measles antibodies during intrauterine life, and therefore are susceptible to measles at an early age. This likewise means that infants in the rural areas studied may have to be vaccinated at an age lower than 9 months. Less than half of the pregnant women have protective levels of measles antibodies; consequently, infants born from most of the tested mothers are likely to have low titers or no measles antibodies at birth, reinforcing the recommendation of vaccination at an earlier age.
Thesis (MS Public Health, Medical Microbiology)--University of the Philippines Manila.
Keywords: Measles -- Vaccination; Immunization of infants